Tricuspid Transcatheter Edge-to-Edge Repair for Severe Tricuspid Regurgitation: 1-Year Outcomes From the TRILUMINATE Randomized Cohort - Tang, Gilbert H L; Hahn, Rebecca T; Whisenant, Brian K; Hamid, Nadira; Naik, Hursh; Makkar, Raj R; Tadros, Peter; Price, Matthew J; Singh, Gagan D; Fam, Neil P; Kar, Saibal; Mehta, Shamir R; et al. (Journal of the American College of Cardiology, 2025)
Tricuspid regurgitation (TR) is a right-sided valvular disease independently associated with morbidity and mortality. The TRILUMINATE Pivotal (Clinical Trial to Evaluate Cardiovascular Outcomes In Patients Treated With the Tricuspid Valve Repair System Pivotal) is the first randomized controlled trial assessing the impact of TR reduction with tricuspid transcatheter edge-to-edge repair (T-TEER). Outcomes from the full randomized cohort of the TRILUMINATE Pivotal trial have not been previously reported, and the additional enrollment may further support the safety and effectiveness of T-TEER through 1 year. The TRILUMINATE Pivotal trial is an international randomized controlled trial of T-TEER with the TriClip device in patients with symptomatic, severe TR. Adaptive trial design allowed enrollment past the primary analysis population. The primary outcome was a hierarchical composite of all-cause mortality or tricuspid valve surgery, heart failure hospitalizations (HFHs), and quality-of-life improvement measured by Kansas City Cardiomyopathy Questionnaire (KCCQ) at 1 year. Between August 21, 2019, and June 29, 2022, 572 subjects were randomized, including the primary cohort (n = 350) and subsequent enrollment (n = 222). Subjects were older (78.1 ± 7.8 years) and predominantly female (58.9%), with atrial fibrillation (87.8%) and prior HFH (23.8%). The primary endpoint was met for the full cohort (win ratio = 1.84; P < 0.0001). Freedom from all-cause mortality and tricuspid valve surgery through 12 months was 90.6% and 89.9% for the device and control groups, respectively (P = 0.82). Annualized HFH rate was comparable between device and control subjects (0.17 vs 0.20 events/patient-year; P = 0.40). A significant treatment effect was observed for change in quality of life with 52.3% of device subjects achieving a ≥15-point KCCQ score improvement (compared with 23.5% of control subjects; P < 0.0001). All secondary endpoints favored T-TEER: moderate or less TR at 30 days (88.9% vs 5.3%; P < 0.0001), KCCQ change at 1 year (13.0 ± 1.4 points vs -0.5 ± 1.4 points; P < 0.0001), and 6-minute walk distance change at 1 year (1.7 ± 7.5 m vs -27.4 ± 7.4 m; P < 0.0001). Freedom from major adverse events was 98.9% for T-TEER (vs performance goal: 90%; P < 0.0001). TriClip was safe and effective in the full randomized cohort of TRILUMINATE Pivotal with significant TR reduction and improvements in 6-minute walk distance and health status. Rates of all-cause mortality or tricuspid valve surgery and HFH through 1 year were not reduced by T-TEER.